Enhancement of the Therapeutic Capacity of Mesenchymal Stem Cells by Genetic Modification: A Systematic Review - Pawitan, Jeanne Adiwinata; Bui, Thuy Anh; Mubarok, Wildan; Antarianto, Radiana Dhewayani; Nurhayati, Retno Wahyu; Dilogo, Ismail Hadisoebroto; Oceandy, Delvac (Frontiers in Cell and Developmental Biology, 2020)
Background: The therapeutic capacity of mesenchymal stem cells (also known as mesenchymal stromal cells/MSCs) depends on their ability to respond to the need of the damaged tissue by secreting beneficial paracrine factors. MSCs can be genetically engineered to express certain beneficial factors. The aim of this systematic review is to compile and analyze published scientific literatures that report the use of engineered MSCs for the treatment of various diseases/conditions, to discuss the mechanisms of action, and to assess the efficacy of engineered MSC treatment. Methods: We retrieved all published studies in PubMed/MEDLINE and Cochrane Library on July 27, 2019, without time restriction using the following keywords: “engineered MSC” and “therapy” or “manipulated MSC” and “therapy.” In addition, relevant articles that were found during full text search were added. We identified 85 articles that were reviewed in this paper. Results: Of the 85 articles reviewed, 51 studies reported the use of engineered MSCs to treat tumor/cancer/malignancy/metastasis, whereas the other 34 studies tested engineered MSCs in treating nontumor conditions. Most of the studies reported the use of MSCs in animal models, with only one study reporting a trial in human subjects. Thirty nine studies showed that the expression of beneficial paracrine factors would significantly enhance the therapeutic effects of the MSCs, whereas thirty three studies showed moderate effects, and one study in humans reported no effect. The mechanisms of action for MSC-based cancer treatment include the expression of “suicide genes,” induction of tumor cell apoptosis, and delivery of cytokines to induce an immune response against cancer cells. In the context of the treatment of noncancerous diseases, the mechanism described in the reviewed papers included the expression of angiogenic, osteogenic, and growth factors. Conclusion: The therapeutic capacity of MSCs can be enhanced by inducing the expression of certain paracrine factors by genetic modification. Genetically engineered MSCs have been used successfully in various animal models of diseases. However, the results should be interpreted cautiously because animal models might not perfectly represent real human diseases. Therefore, further studies are needed to explore the translational potential of genetically engineered MSCs.